Simultaneous determination of hexabromocyclododecanes, polybrominated diphenyl ethers, and dechlorane-related compounds in boxed sushi meals using a developed analytical method - Sato, Tamaki; Tobiishi, Kazuhiro; Hori, Tsuguhide; Tsutsumi, Tomoaki; Akiyama, Hiroshi; Matsui, Toshiro (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2023)
We investigated the concentrations of halogenated flame retardants (HFRs), which include hexabromocyclododecanes (HBCDDs), polybrominated diphenyl ethers (PBDEs), and dechloranes and related compounds (DRCs), in 25 typical ready-made boxed sushi meals (each divided into seafood and non-seafood portions) using a developed simultaneous analytical method involving accelerated solvent extraction and gel permeation chromatographic separation. The developed method yielded good recoveries of surrogates (72–122 %). HBCDDs, PBDEs, and DRCs were detected in all seafood portions. While DRCs were also frequently detected in non-seafood portions, HBCDDs and PBDEs were hardly detected. The estimated dietary intakes of HBCDDs, PBDEs, and DRCs from boxed sushi meals were well below the corresponding health-based guideline values. In conclusion, our study suggests that the intake of HFRs from boxed sushi meals poses low concern for consumer health and that the developed simultaneous analytical method is highly useful for determining HFRs in seafood-based meals.